Cpx-signalling facilitates Hms-dependent biofilm formation by Yersinia pseudotuberculosis - Dharmender K. Gahlot; Sun N. Wai; David L. Erickson; Matthew S. Francis (npj Biofilms and Microbiomes, 2022)
Abstract Bacteria often reside in sessile communities called biofilms, where they adhere to a variety of surfaces and exist as aggregates in a viscous polymeric matrix. Biofilms are resistant to antimicrobial treatments, and are a major contributor to the persistence and chronicity of many bacterial infections. Herein, we determined that the CpxA-CpxR two-component system influenced the ability of enteropathogenic Yersinia pseudotuberculosis to develop biofilms. Mutant bacteria that accumulated the active CpxR~P isoform failed to form biofilms on plastic or on the surface of the Caenorhabditis elegans nematode. A failure to form biofilms on the worm surface prompted their survival when grown on the lawns of Y. pseudotuberculosis. Exopolysaccharide production by the hms loci is the major driver of biofilms formed by Yersinia. We used a number of molecular genetic approaches to demonstrate that active CpxR~P binds directly to the promoter regulatory elements of the hms loci to activate the repressors of hms expression and to repress the activators of hms expression. Consequently, active Cpx-signalling culminated in a loss of exopolysaccharide production. Hence, the development of Y. pseudotuberculosis biofilms on multiple surfaces is controlled by the Cpx-signalling, and at least in part this occurs through repressive effects on the Hms-dependent exopolysaccharide production.